Perbandingan Tear Film Pre dan Post Operasi Fakoemulsifikasi pada Pasien Katarak di Rumah Sakit Mata Makassar dengan Tes Break Up Time Tahun 2025 - Annisa Al-rezky; Andi Senggeng Relle; Nursapriani (RS Mata Makassar, 2025)
One of the causes of dry eye is eye surgery such as phacoemulsification. Failure in the tear film's homeostatic mechanism can lead to a decrease in the quality and quantity of tears, resulting in reduced tear film stability. Aim to determine changes in the tear film before and after phacoemulsification surgery in cataract patients at Makassar Eye Hospital using the tear break-up time (TBUT) test in 2025. This study used a one-group pre-test and post-test design. It was a quantitative study with a pre-experimental approach. The sample in this study was selected using purposive sampling, involving 96 individuals who underwent phacoemulsification surgery. The results of the paired t-test for the comparison of tear film quality before and after phacoemulsification surgery in the first week showed a p-value of 0. 000 < 0.05, indicating a highly significant change in tear film among cataract patients before and after phacoemulsification surgery in the first week. The comparison of tear film before and after phacoemulsification surgery in the third week yielded a p-value of 0.028 < 0.05, indicating a significant change in tear film among cataract patients before and after phacoemulsification surgery. There is a significant change in tear film pre- and post-phacoemulsification surgery in the first week, and in the third week, there is a significant change in cataract patients at Makassar Eye Hospital based on TBUT values.